Analgesia and anesthesia for the ill or injured dog and cat - Mathews, Karol A., 1946-; Sinclair, Melissa; Steele, Andrea M.; Grubb, Tamara (Hoboken, NJ : Wiley, 2018)
Analgesia and Anesthesia for the Ill or Injured Dog and Cat provides a comprehensive guide to anesthesia and pain management protocols, specifically tailored to ill or critically injured dogs and cats. -Provides fast access to anesthesia and pain management protocols specifically tailored to ill or critically injured dogs and cats -Takes a case-based structure to make it easy to find and apply relevant information -Presents step-by-step clinical procedures and techniques -Supplies concise, relevant background information for all drugs recommended in the protocols, highlighting recommendations and cautions for specific patient conditions -Includes detailed information for geriatric, pregnant, nursing, and pediatric patients and those with cardiac, liver or kidney pathology.
A. Afferent and Efferent InnervationsB. Autonomic Nervous System [4]; C. Central Processing [2]; D. Peripheral Sensitization; E. Central Sensitization (Inflammation-Induced); II. Clinical Relevance of Physiology to Pharmacology; A. Dorsal Horn Targets for Analgesics [3]; B. Peripheral Sensitization Targets for Analgesics; C. Reduction/Modulation of the Transmission of Nociceptive Information; D. Epidural Site for Analgesic Administration; III. Sources of Abdominal Pain; A. Gastrointestinal System; B. Urogenital System; IV. Pelvis and Perineum [3, 5]; A. Pelvis
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Veterinary anesthesia; Analgesia; Pain -- Treatment; Dogs -- Diseases; Cats -- Diseases; Analgesia; Cats -- Diseases; Dogs -- Diseases; Pain -- Treatment; Veterinary anesthesia; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Analgesia -- veterinary; Anesthesia -- veterinary; Pain Management -- veterinary; Dogs -- injuries; Cats -- injuries; Electronic books